KEPEMIMPINAN PEREMPUAN PERSPEKTIF MUFASSIR NUSANTARA - Tohet, Moch.; Maulidia, Lathifatul (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
The phenomenon that occurred in the archipelago in the Modern Era as it is today, women have appeared to be